Antimicrobial activity of dietary supplements based on bacterial lysate of Lactobacillus rhamnosus DV - Penchuk, Yurii; Savytska, Maryana; Kobyliak, Nazarii; Ostapchenko, Danylo; Kolodiy, Igor; Onysenko, Svitlana; Tsyryuk, Olena; Korotkyi, Oleksandr; Grygoriev, Fedir; Falalyeyeva, Tetyana (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction According to WHO, antibiotic resistance is increasing to hazardous levels worldwide. Candidiasis often occurs after taking antibiotics. Therefore, antibiotic resistance is a global problem and searching for antibacterial agents is necessary. Aim To determine the antimicrobial activity of bacterial lysate of Lactobacillus (L.) rhamnosus DV separately and with plant extracts against bacterial and yeast test cultures. Material and methods Antimicrobial activity of Del-Immune V® (cell wall and DNA fragments from a L. rhamnosus DV) separately and with cinnamon, beetroot, and blackcurrant extracts was determined by the minimum inhibitory concentration (MIC). Twofold serial dilutions determined the MIC in previously prepared meat-peptone broth (MPB) for bacteria and liquid wort for yeast. In the study, gram-negative (Escherichia coli IEM-1, Proteus vulgaris PА-12, Pseudomonas sp. MI-2, L. rhamnosus 13/2) and gram-positive (Bacillus (B.) subtilis BТ-2, Staphylococcus aureus BМС-1) bacteria, as well as yeast (Candida (C.) albicans D-6, C. tropicalis PE-2, C. utilis BVS-65) were used as test cultures. Results The MIC for the studied bacterial test cultures after application of L. rhamnosus DV bacterial lysates was from 1.0 ± 0.05 mg/mL to 12.5 ± 0.63 mg/mL, which was significantly less than that of the thermally inactivated control (MIC from 125.0 ± 6.25 mg/mL to 250.0 ± 12.5 mg/mL). B. subtilis BT-2 culture was the least sensitive to the action of the bacterial lysate (MIC—12.5 ± 0.63 mg/mL). It showed the best antibacterial and antifungal effect bacterial lysate with the phytonutrient blackcurrant. Conclusions It was demonstrated that bacterial lysate of lactic acid bacteria L. rhamnosus DV exhibits antibacterial and antifungal properties during direct contact with pathogenic agents.